2020
DOI: 10.1017/s1479262120000295
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of resistance to stemphylium blight in interspecific recombinant inbred lines derived from Lens culinaris × Lens ervoides

Abstract: Cultivated lentil suffers yield loss from stemphylium blight, caused by Stemphylium botryosum Wallr. Identification of sources of stemphylium blight resistance and knowledge of the mode of inheritance of resistance are important for developing resistant cultivars. The interspecific recombinant inbred line (RIL) population developed from a cross between the moderately resistant parent Lens culinaris cv. ‘Eston’ and the resistant parent L. ervoides (Brign.) Grande accession IG 72815 was evaluated for stemphylium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
3
8
0
Order By: Relevance
“…None of the LABC-01 individuals had significantly less disease than the resistant parent LR-59-81 (Supplementary Table S1). This observation is consistent with the findings of Adobor et al . (2020) who also reported the absence of resistant transgressive segregants in L. ervoides interspecific population screened for stemphylium blight resistance in the greenhouse, growth chamber and the field conditions.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…None of the LABC-01 individuals had significantly less disease than the resistant parent LR-59-81 (Supplementary Table S1). This observation is consistent with the findings of Adobor et al . (2020) who also reported the absence of resistant transgressive segregants in L. ervoides interspecific population screened for stemphylium blight resistance in the greenhouse, growth chamber and the field conditions.…”
Section: Resultssupporting
confidence: 94%
“…None of the LABC-01 individuals had significantly less disease than the resistant parent LR-59-81 (Supplementary Table S1). This observation is consistent with the findings of Adobor et al (2020) who also reported the absence of resistant transgressive segregants in L. ervoides interspecific population screened for stemphylium blight resistance in the greenhouse, growth chamber and the field conditions. A high proportion of the LABC-01 individuals (144) had similar disease severity when compared to the resistant parental line LR-59-81, indicating that resistance genes were transferred from the resistant parent to LABC-01 individual lines ( Supplementary Table S1).…”
Section: Resultssupporting
confidence: 93%
“…This was further confirmed in the interspecific L . culinaris × L. ervoides RIL population LR-26 by Adobor et al (2020). QTLs consistently detected across different environments are ideal for introgression and use in breeding programs because crops with such QTLs are more likely to display a resistant phenotype in more than one environment (El-Soda et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, the pathogen has steadily increased in virulence and is currently responsible for up to 80% lentil yield losses [ 7 ]. Furthermore, over recent decades, its incidence has also increased in different regions of the world, notably in Canada [ 8 ], India, Nepal and North America [ 3 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The optimization of inoculum production and of the inoculation method as a whole is therefore urgently needed to allow large-scale screening of lentil germplasm and populations. Recent studies have resorted to mycelial suspensions for artificial inoculations [ 9 ]. However, a comprehensive understanding of the impact of inoculum type, inoculum concentration, growth conditions and their interaction with genotype has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%